Sedum dasyphyllum subsp. glanduliferum: a new addition for the flora of northwestern Spain - Ferreiro-Lera, Giovanni-Breogán; Penas, Ángel; Alonso-Redondo, Raquel; Álvarez-Santacoloma, Aitor; González-Pérez, Alejandro; Ochoa-Ramos, Norma-Yolanda; del Río, Sara (Mediterranean Botany, 2025)
Sedum dasyphyllum L. has a controversial infraspecific treatment, with three subspecies distinguished based on the abundance of glandular indumentum. Sedum dasyphyllum L. subsp. glanduliferum (Guss.) Nyman, characterized by the presence of abundant glandular hairs, was considered a subspecies with a southern tendency, with very few and unclear records in the northwestern Iberian Peninsula. In the present study, 56 herbarium sheets from the LEB FCO and SANT herbaria were assigned to the taxa Sedum dasyphyllum L. and Sedum dasyphyllum L. subsp. dasyphyllum were analyzed. Of these, 45 were re-assigned to Sedum dasyphyllum L. subsp. glanduliferum (Guss.) Nyman, constituting the first records for this taxon in the provinces of León, Lugo, Oviedo, Orense, Palencia, and Santander. Moreover, five sheets were reassigned to Sedum dasyphyllum L. subsp. dasyphyllum, while another five retained their original assignment (Sedum dasyphyllum L. subsp. dasyphyllum). The populations are now identified as Sedum dasyphyllum L. subsp. glanduliferum (Guss.) Nyman do not appear to occupy more southern enclaves or southern slopes, although they are, on average, found at higher altitudes within the study area. Keywords: Glandular indument, LEB herbarium, northwestern Iberian Peninsula, preserved plants, province of León, Sedum dasyphyllum subsp. glanduliferum.